Research on Fluid-solid Coupling Numerical Simulation for Debris Transport in Containment Based on CFD-DEM Method - ZHANG Fengtao, ZHANG Jing, WU Yingwei, HE Yanan, TIAN Wenxi, QIU Suizheng (Yuanzineng kexue jishu)
When a loss of coolant accident (LOCA) occurs in a nuclear power plant, the rupture of the coolant leads to a rapid introduction of many debris into the containment vessel. This not only significantly increases the pressure drop at the filter screen but also hinders the circulation of cooling water in the safety systems, thereby affecting the safe operation of the reactor after the accident. In order to accurately obtain the transportation process of debris inside the containment and analyze the impact of debris on the water circulation and hydraulic characteristics after the accident, numerical simulation calculations on the debris transportation were carried out in this paper. Based on a typical debris transport experimental setup, computational fluid dynamics (CFD) and discrete element method (DEM) was combined to establish a debris transport analysis model. By comparing the numerical simulation results with the debris deposition test and migration test results, the accuracy of the constructed debris transport numerical simulation model was verified. Based on the established numerical analysis model, the migration process of thermal insulation cotton debris was simulated at inlet flow rates of 1 m/s and 2 m/s, and the migration process mechanism of the debris and the accumulation characteristics of the debris were analyzed. The results indicate that flow velocity and debris accumulation morphology significantly influence debris transport behavior and share. At low flow rates, the fluid driving force on the debris in the flow channel is insufficient to overcome the viscosity and friction resistance, resulting in the accumulation of debris at the front of the flow channel center. Under the combined influence of the solid-liquid phase force and the viscosity, the debris forms three different debris accumulation types from the flow inlet to the outlet: accumulation area, void area, and obstacle area. At this time, basically no debris is transported to the rear end of the structure. At high flow velocities, the transport distance of debris increases, with accumulation occurring in the low-speed recirculation zone in front of the structural parts, and the recirculation effects at the edges of the flow channel cause the debris to move toward the edges. The impact of debris accumulation on the flow and pressure fields in the flow channel is localized, primarily manifested as a decrease in flow velocity at the debris accumulation site and an increase in pressure drop caused by localized positive pressure regions at the leading surface. The findings provide theoretical foundations and technical support for the optimization design and safety assessment of debris transport processes within nuclear power plants.